Analysis of Students' Problem-Solving Abilities in Learning with an Ethnoscience-Based Socio-Scientific Issues (SSI) Approach (UNIVERISTAS PGRI MADIUN, 2024)
Ethnoscience-based learning is limited to constructing community knowledge into scientific knowledge, it needs to be directed at solving problems that occur in local potential/culture. The research aims to analyze students' problem-solving abilities in learning using the Ethnoscience Based Socio Scientific Issues (SSI) Approach. The research uses a quantitative approach, true experimental method, and pretest-posttest control group design type. The research sample was taken using the simple random sampling method. Problem-solving ability is measured using description questions and analyzed using a percentage scale. To see the difference in problem-solving abilities between the experimental class and the control class, the t-test was used and to see how big the difference was, the Gain test was used. The research results showed that 81% of students' problem-solving abilities were in the good category. The results of the t-test show that there is a difference in problem-solving abilities between classes that apply the ethnoscience-based Socio Scientific Issues (SSI) approach and those that do not, as indicated by the tcount of 7.396 which is greater than the ttable of 2.045. The difference in students' problem-solving abilities is 0.74 in the high category. The impact of being trained in the stages of problem-solving on each topic of local problems, students have good problem-solving abilities.